ANALYSIS OF POLITICAL PARTICIPATION AND ONLINE PUBLIC DISCOURSE ON DEMOCRACY ISSUES DURING THE 2024 PRESIDENTIAL ELECTION DEBATE ON YOUTUBE - Auliya, Asti Nurul; Nasiwan, Nasiwan; Perdana, Dimes Akbar (International Journal of Social Service and Research, 2025)
This study aims to explore (1) the influence of polarization of public opinion on YouTube social media on the 2024 presidential debate, (2) the public's response to the issue of democracy raised by the presidential candidate pair, and (3) the impact of YouTube use on political participation in the 2024 presidential election. Using a qualitative approach with the critical discourse analysis (CDA) method, this study analyzes online conversations about democracy issues in the 2024 election debate. The data was obtained through web scraping using Python and analyzed using the NVivo application to identify keywords and conduct sentiment analysis. Researchers play the role of the main instrument in the research process, ensuring the validity of data through systematic analysis. The analysis process includes the identification of debate videos, transcription of comments, classification, and analysis of participation patterns. The results of the study show that (1) the polarization of public opinion occurs through moderate debates related to the presidential candidate's ideas about democracy, human rights, and social justice; (2) the response of the public reflects the important role of YouTube in shaping understanding of democratic issues; and (3) the use of social media, especially YouTube, contributes significantly to political participation, making these platforms a tool for discussing and expressing political views that can influence the outcome of elections.